The correct genus for the Afrotropical woodpeckers Campethera caroli and Campethera nivosa (Aves: Piciformes, Picidae) - Dowsett, Robert J.; Gregory, Steven M.s. (Zootaxa, 2020)
We argue that the correct generic name for the Afrotropical woodpeckers usually known as Campethera caroli and Campethera nivosa (Aves: Piciformes, Picidae) should be Pardipicus Bonaparte, 1854, and we choose and propose Chloropicus caroli Malherbe, 1852 as type species. Fuchs et al. (2018) had suggested Stictopicus Malherbe, 1861, following Wolters (1977), but that genus has as type species Picus nubicus Boddaert, 1783 (= Campethera nubica).